Acquisition of the first word forms in Croatian - Babić, Zrinka (Array, 1996)
Besides interindividual differences, children posses different word forms in their lexicon due to the structural differences among languages. Because of its rich morphology Croatian proves to be an appropriate language to analyze various influences on children word forms' production. In addition to structural influences of the input language, Croatian data show that the first word forms are strongly context dependent.